Effects of Social Connectedness on the Sharing of Employee-Created Content - Zhang, Xueting; Chen, Man (Frontiers in Psychology, 2022)
With the popularity of social network platforms (e.g., Facebook, WeChat), users can easily build social connections with others, create content, and even forward or share content. While previous studies on content sharing shed light on either content creator or receiver, this paper is to investigate whether, when, and how the social connectedness of content creator (i.e., employee) and receiver (i.e., employee’s friend) jointly influence the sharing likelihood of receiver. We conducted a field study on the largest social media platform and two experiments in China. Study 1 found that well-connected receivers prefer to share content from well-connected employee, and poorly-connected receivers prefer to share content from poorly-connected employee. But, if the content contains promotional information, well-connected receivers are less likely to share it from the well-connected employee. Studies 2 and 3 confirmed these findings and verified that self-enhancement motivation acts as a mediator. The findings suggest that firm should choose the “right” employees who will send content to their “right” friends, and caution about the crowd-out effect of promotional content. We provide new insights into the joint effects of creator and receiver, the moderating role of promotional content, and the mediating role of self-enhancement, which enriches both viral marketing and social media literature.